O extermínio da juventude popular no Brasil: uma análise sobre os “discursos que matam” - MORAIS, Romulo Fonseca (Universidade Federal do Pará, 2018)
In Brazil, it's terrifying the number of people killed every year. However, some aspects call the attention in this scenario: the statistics show a colossal number of people from the same social group, age group and ethnicity being annihilated daily. The black youth and or nearly black because it's too poor has been part of more than half the number of deaths. From this context it is practically inevitable not problematize the practice of the daily extermination against this segment of the population. The most visible part of that extermination practice can be seen in the performance of the criminal justice system, especially in the intense criminalization of the youth at the present stage of neoliberalism. Assuming that there is no extermination without the construction of discourses that legitimize it ( "truth discourses that can kill," according to Foucault), the research's main problem is to know how the practice of extermination of the black youth is performed and legitimized through speeches around the lives of young people in Brazil. Using as reading keys the contributions of critical criminology and biopower, we intend to analyze how these discourses in the social body and in an institution (childhood and youth justice) is (re)produced and how they operate in the legitimization of death, becoming "speeches that they kill". From this, we aim to discuss these deaths not as simple random and isolated events but as part of an permanent process of criminalization and extermination of popular youth in Brazil.